Reading the Market : Genres of Financial Capitalism in Gilded Age America - Knight, Peter, 1968- (Book collections on Project MUSE., 2016)
Americans pay famously close attention to "the market", obsessively watching trends, patterns, and swings and looking for clues in every fluctuation. In Reading the Market, Peter Knight explores the Gilded Age origins and development of this peculiar interest. He tracks the historic shift in market operations from local to national while examining how present-day ideas about the nature of markets are tied to past genres of financial representation. Drawing on the late nineteenth-century explosion of art, literature, and media, which sought to dramatize the workings of the stock market for a